2016
DOI: 10.1024/0300-9831/a000426
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation in Adults with Vitamin D Deficiency and Its Effect on Metabolic Syndrome – A Randomized Controlled Study

Abstract: In this study the relationship between vitamin D supplementation and MetS or IR was not established. Whether achieving vitamin D sufficiency in large population-based trials with a longer duration would produce more favorable results needs to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Eight of them showed no difference in BMI after the intervention Frontiers in Pharmacology frontiersin.org compared to baseline values in the experimental group. Only 1 trail showed a significant reduction after VDS treatment (Mahmood et al, 2016). Meanwhile, 2 trails also assessed WHR (Salekzamani et al, 2016;Shidfar et al, 2019).…”
Section: Results Of the Included Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight of them showed no difference in BMI after the intervention Frontiers in Pharmacology frontiersin.org compared to baseline values in the experimental group. Only 1 trail showed a significant reduction after VDS treatment (Mahmood et al, 2016). Meanwhile, 2 trails also assessed WHR (Salekzamani et al, 2016;Shidfar et al, 2019).…”
Section: Results Of the Included Rctsmentioning
confidence: 99%
“…The assessment results of the bias risk in the included RCTs are shown in Figure 2. According to the Cochrane criteria, the Frontiers in Pharmacology frontiersin.org Mahmood et al, 2016;Salekzamani et al, 2016;Maktabi et al, 2017;Pragya et al, 2021), while this was unclear in the other studies. Blinding of participants was not clear in 4 trails (Farag et al, 2019;Corcoy et al, 2020;Imanparast et al, 2020;Cojic et al, 2021), since they did not mention the randomization method.…”
Section: Assessment Of Bias Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The controversy regarding the vitamin D–metabolic syndrome–insulin resistance relationship is an open and much-debated issue. Some studies do not seem to support this hypothesis, unlike others [ 40 , 41 ]. Recently, in a double-blind, randomized clinical trial (RCT) [ 41 ], albeit on a modest sample (44 patients enrolled for 3 months), insulin resistance, glucose homeostasis, and metalloproteases (MMP-9) were evaluated in obese subjects (BMI: 30–40 kg/m 2 ) with a deficiency of vitamin D (25 (OH)-D: ≤50 nmol/L; ≤20 ng/mL) in which, with double-blind randomization, a high dose of vitamin D3 (50,000 U/week) was administered for 3 months together with a weight loss diet.…”
Section: Role Of Vitamin D In Diabetes Mellitus Metabolic Syndrome and Obesitymentioning
confidence: 86%
“…For example, some studies have shown an inverse association between the incidence of MetS and serum vitamin D levels [17][18][19][20], while others have failed to find such an association [21][22][23][24][25]. Furthermore, the association between vitamin D status and MetS was observed mostly in cross-sectional studies, but not in the clinical trial [ 26] or in longitudinal studies [ 27,28].…”
Section: Introductionmentioning
confidence: 99%